Inequality of opportunity in South Africa - Booysen, Andrid Angelique (My University, 2023)
Recent studies conducted in South Africa and other developing countries show that measuring the “unfair inequalities” in society (such as with income) that have an effect on one’s abilities to achieve certain outcomes, can assist in better understanding total inequality. Statistics South Africa (Stats SA) is the government agency that is responsible for measuring and reporting inequality in the country. The purpose of this research is to contribute in providing an alternative view on how Stats SA can measure and report inequality in South Africa. The study adopts the ex-ante view when measuring inequality of opportunity. Data used for the study was sourced from the Living Conditions Survey (LCS). The variables used in the study were divided into outcome, circumstance and effort. The outcome or dependent variable used for this research was individual income annualised and adjusted for inflation. Results from the study show that individual employment status, individual years of schooling, race, parental educational level and employment status, sex of individual at birth and place of residence had the biggest effect on individual income in South Africa
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Management in Development and Economics to the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Unfair inequalities; South Africa; Inequality; UCTD; Statistics South Africa; SDG-5: Gender equality; SDG-8: Decent work and economic growth